Assessing soil fertility status of rehabilitated degraded tropical rainforest - Jamaluddin, Aiza Shaliha; Abdu, Arifin; Abdul Hamid, Hazandy; Akbar, Mohd Hadi; Banga, Trevor Saga; Jusop, Shamshuddin; Nik Ab. Majid, Nik Muhamad (Science Publications, 2013)
An assessment of forest rehabilitation program in relation to soil fertility status by using soil indices could provide fundamental information on soil suitability for species preferences and improve the effective technique for future rehabilitation program in tropical rainforests. This study was conducted in order to characterize the soil properties and identifying the soil fertility status of rehabilitated and secondary forests. Soil samples were collected in year 2009 at rehabilitation forests (20 years after planting) and secondary forest of Nirwana Forest Reserve, Universiti Putra Malaysia (UPM) Bintulu Campus, Sarawak, Malaysia. The rehabilitation plots were planted with mixed dipterocarp and non-dipterocarp species since 1991. Prior to conversion of the areas into various land use types, the rehabilitation and secondary forests areas were considered as natural forests and subsequently subjected to forest logging with Selective Management System (SMS) in 1980s.The plot size for each site was 20×20 m for 18 experimental sites (at different ages after planting) were established, followed by soil sampling at 0-15 cm and 15-30 cm depth randomly using soil auger. Standard soil analysis for physical and chemical properties was used to analyze the soil samples. The soil fertility status was evaluated using two indices, namely Soil Fertility Index (SFI) and Soil Evaluation Factor (SEF) for both rehabilitated and secondary forests. The results showed that there were significant differences (p<0.05) in pH (water and KCl), exchangeable Mg, Na, Al and ammonium and granule composition (clay, silt and sand) between depths. The PCA result of 70% total variability (OM, TOC, TC and CEC) score in PC1 shows positive relationship, explaining nutrients in the soil stored in the organic matter in the surface soils. The correlation analysis indicated that there were positive relationship (p<0.05) between OM and TC, CEC and exchangeable Al for surface soils. We found that the selected physico-chemical properties had a significant differences based on the age of planting of rehabilitated forests. For subsurface soils, correlation between exchangeable Al and OM and CEC shows strong positive relationship, indicating that negative charge derived from organic materials plays important roles for cation retention capacity. The SFI and SEF for rehabilitation forests showed higher value as compared to secondary forests, indicating forest rehabilitation had improved the soil fertility status of degraded forestland. In conclusion, both rehabilitated and secondary forests have significant differences based on the selected physical and chemical properties. Moreover, the soil fertility status at rehabilitated plots was higher than secondary forest, which is proved that the forest rehabilitation technique is a suitable planting technique for rehabilitating and replenishing soil fertility status of abandoned degraded shifting cultivation land.